Synthesis and Evaluation of Urethane Polymers from PET Waste - Jalal, Mahir A. (Sulaimani Journal for Pure and Applied Sciences, 2015)
This study is engaged in synthesis of novel monomer bis(2-hydroxyethyl) by chemical recycling of PET waste using excess of thioglycol in prescience of (0.5%) zinc acetate as catalyst. Best yield of monomer was obtained (40%) when using 1:6 PET to thioglygol molar ratio and 16 hours reaction time. The thiolyzed products were purified and characterized by FTIR, 1H NMR and CHNS analysis and these characterizations were proved that nucleophilic attack to carbonyl groups of PET backbone was achieved by thiol groups instead of hydroxyl groups of thioglycol. Also, urethane polymers were prepared by reaction of various weight ratios of bis(2-hydroxyethyl) thioterephthalatepoly(ethylene glycol) mixtures with 2,4-toluene diisocyanate monomer. Good mechanical compression of polyurethane polymers were obtained and evaluated showing transition properties from rigid to flexible urethane polymers.
Keywords: Chemical recycling; Depolymerization; Thiolysis; PET waste; Thioglycol; 2mercaptoethanol; Polyurethane